Польская тема в произведениях Василия Аксенова - Karlina, Natalia (My University, 2011)
In this article the author suggests an unexpected thematic turn (the Polish turn) of analysis of V. Aksyonov's works. The analysis of the novel Moscow Saga (1994), for example, concerns the involvement of novel's characters in solving “the Polish question”. Aksyonov's attitude to the matter coincides with A. Herzen's reaction to tragic events of 1863. But both A. Herzen and V. Aksyonov wrote not only about Russian-Polish war conflicts. These authors recognized also Polish charm.
The Polish theme in Vassily Aksyonov's works
Polski temat w utworach Wasyla Aksionowa